ANALISIS PENERAPAN ASAS PRADUGA TIDAK BERSALAH TERHADAP PELAKU TINDAK PIDANA PENCURIAN DENGAN KEKERASAN - Nanci Yosepin Simbolon; Obedi Laia (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2019)
One of the principles of criminal law in Indonesia is the presumption of innocence. The principle of presumption of innocence is the principle whereby a person is considered innocent until the court finds him guilty. In criminal cases of theft with violence, law enforcers must implement the presumption of innocence at every level of examination of a suspect / defendant, both at the level of investigation and at the trial at court. This research uses the normative legal research method. One of the studies in normative legal research is the principles of law. Normative legal research or library research is a study that examines document studies, namely a case study on the decision of the Medan District Court No. 3194 / Pid.B / 2019 / PN Mdn. The author uses analysis of interpretation and syllogism to describe or explain the legal issues under study. Based on the research and discussion conducted by the author, namely the analysis of the application of the presumption of innocence to perpetrators of violent theft (decision study No. 3194 / Pid.B / 2019 / PN Mdn shows that the application of the presumption of innocence begins at the level of investigation that suspects someone as the perpetrator of a criminal act and placing the suspect's status at the police level and the defendant's status at court proceedings.